Phase I trial of adjuvant mature autologous dendritic cell/allogeneic tumor lysate vaccines in combination with temozolomide in newly diagnosed glioblastoma. Issue 1 (24th June 2022) - Parney, Ian F; Anderson, S Keith; Gustafson, Michael P; Steinmetz, Susan; Peterson, Timothy E; Kroneman, Trynda N; Raghunathan, Aditya; O'Neill, Brian P; Buckner, Jan C; Solseth, Mary; Dietz, Allan B
Abstract: Background: Glioblastoma (GBM) has poor prognosis despite aggressive treatment. Dendritic cell (DC) vaccines are promising, but widespread clinical use has not been achieved, possibly reflecting manufacturing issues of antigen choice and DC potency. We previously optimized vaccine manufacture utilizing allogeneic human GBM tumor cell lysate and potent, mature autologous DCs. Here, we report a phase I study using this optimized DC vaccine in combination with standard therapy. Methods: Following surgical resection and radiation with concurrent temozolomide (TMZ), newly diagnosed adult GBM patients received intradermal DC vaccines plus TMZ. Primary endpoints were safety and feasibility. Immune and treatment responses were recorded. Results: Twenty-one patients were enrolled in this study. One progressed between leukapheresis and vaccine manufacture. Twenty patients received treatment per protocol. Vaccine doses (≥15) were generated following a single leukapheresis for each patient. No dose-limiting vaccine toxicities were encountered. One patient had symptomatic, histologically proven pseudoprogression. Median progression-free survival was 9.7 months. Median overall survival was 19 months. Overall survival was 25% at 2 years and 10% at 4 years. One patient remains progression-free 5 years after enrollment. Specific CD8 T-cell responses for the tumor-associated antigen gp100 were seen post-vaccination. Patients entered the trial with a leukocyte deficit compared to healthy donors which partly normalized over the course of therapy. Conclusions: This vaccine platform is safe and highly feasible in combination with standard therapy for newly diagnosed patients. Imaging, histological, survival, and immunological data suggest a positive biological response to therapy that warrants further investigation.